One Century from “The Analysis of Mind” (1921) by Bertrand Russell - José E. García (Revista de Psicología, 2022)
In 1921 The analysis of mind of the English philosopher Bertrand Russell was published, a volume that was conceived a few years after John B. Watson defined the new orientation known as behaviorism. In the book, Russell undertook a discussion of some of the central concepts proposed by Watson, putting them in relation to other topics of interest within his own philosophical and psychological approach, such as the problem of consciousness and the theory of desires. Russell's work provided important support for emerging behaviorism. A century after its publication, this article assesses its general importance both in the history of psychology and behaviorism. Likewise, the way in which Russell conceptualized the main aspects of behavioral theory is analyzed. The article has a theoretical and review character, based on a pertinent use of the primary sources related to the subject.